2014
DOI: 10.5455/msm.2014.26.100-103
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Near Work and Myopia Progression in Student Population

Abstract: AimTo determine relation between near work and myopia progression in student population. Causes of myopia occurrence are not sufficiently explained.MethodsThis retrospective-prospective, descriptive research included 100 students with verified myopia up to -3 Dsph. Ophthalmological examination and measurement diopter-hours variable (Dh) were done twice, in the period from January 2011 until January 2012.ResultsA multivariate regression analysis of impact on the difference of distance visual acuity without corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
1
27
0
4
Order By: Relevance
“…In another study, PA led to a decrease in myopia, when comparing the measurements before and after PA (Muhamedagic et al. ). The study included 100 myopic university students from Bosnia and Herzegovina, who were asked about their PA patterns and tested physically.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, PA led to a decrease in myopia, when comparing the measurements before and after PA (Muhamedagic et al. ). The study included 100 myopic university students from Bosnia and Herzegovina, who were asked about their PA patterns and tested physically.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported amount of NITM in individuals without vision dysfunctions has been reported from 0.11 D to 0.90 D with a mean of about 0.30 D [6,7,12]. NITM has been mentioned as one of the main environmental factors that play a significant role in the development of late-onset myopia [13,14]. Myopia prevalence has reached epidemic levels in Asia and currently is increasing also in Europe [15,16], In scientific literature, attention and interest towards near work-induced changes in refraction has been decreasing with the time.…”
Section: Near Work-induced Refraction Shiftsmentioning
confidence: 99%
“…The concept that myopia evolved from the extensive use of the eyes during near vision was credited to Cohn in 1886, but has been mentioned as early as 1611 by Kepler. 17,18 Recent studies have demonstrated that myopia is associated with several traits and environments, including intelligence, [19][20][21] academic advancement, 20,[22][23][24][25] avocations requiring near vision use, [26][27][28][29][30] professional school, 31,32 caged versus free-ranging animals 33 and people confined to restricted spaces such as submarines. 34,35 The implication of most of these studies is that the greater the time spent performing near work results in an increased incidence of myopia.…”
Section: Introductionmentioning
confidence: 99%